Possible Genetic Determinants of Response to Phenytoin in a Group of Colombian Patients With Epilepsy - Calderon-Ospina, Carlos Alberto; Galvez, Jubby Marcela; López-Cabra, Claudia; Morales, Natalia; Restrepo, Carlos Martín; Rodríguez, Jesús; Aristizábal-Gutiérrez, Fabio Ancízar; Velez-van-Meerbeke, Alberto; Laissue, Paul; Fonseca-Mendoza, Dora Janeth (Frontiers in Pharmacology, 2020)
Background: Epilepsy is a serious health problem worldwide. Despite the introduction of new antiepileptic drugs (AEDs) almost 30% of these patients have drug-resistant forms of the disease (DRE), with a significant increase in morbi-mortality. Objective: Our objective was to assess the impact of some genetic factors and its possible association with treatment response and adverse drug reactions (ADRs) to phenytoin in 67 adult Colombian patients with epilepsy. Methods: We conducted an analytical, observational, prospective cohort study to screen four polymorphisms in pharmacogenes: CYP2C9*2 c.430C>T (rs1799853), CYP2C9*3 c.1075A>C (rs1057910), ABCB1 c.3435T>C (rs1045642) and SCN1A IVS5-91 G>A (rs3812718), and their association with treatment response. Patients were followed for one year to confirm the existence of DRE (non-response) and ADRs using an active pharmacovigilance approach, followed by a consensus in order to classify ADRs according to causality, preventability, intensity and their relation with phenytoin dose, the duration of treatment, and susceptibility factors (DoTS methodology). Results: A little more than half of evaluated subjects (52,2%) were non-responding to phenytoin. Regarding the genotype-phenotype correlation there was no association between polymorphisms of SCN1A and ABCB1 and DRE (non-response) (p = 0,34), and neither with CYP2C9 polymorphisms and the occurrence of ADRs (p = 0,42). We only found an association between polymorphic alleles of CYP2C9 and vestibular-cerebellar ADRs (dizziness, ataxia, diplopia and dysarthria) (p = 0.001). Alleles CYP2C9- c.430C>T and CYP2C9- c.1075A>C were identified as susceptibility factors to ADRs in 24% of patients. Conclusions: Polymorphic alleles of CYP2C9 were highly predictive of vestibular-cerebellar ADRs to phenytoin in our study (p = 0,001). However, the genetic variants CYP2C9-c.430C>T, CYP2C9- c.1075A>C, ABCB1-c.3435T>C and SCN1A-IVS5-91G>A, were not associated with treatment response in our study.